Cylindrical 3D printed configurable ultrasonic lens for subwavelength focusing enhancement; Scientific Reports; Vol. 10, iss. 1 - Castineira-Ibanez S. Sergio; Tarrazo-Serrano D. Daniel; Uris A. Antonio; Rubio C. Constanza; Minin O. V. Oleg Vladilenovich; Minin I. V. Igor Vladilenovich (2020, 2020)
Title screen